Attachment Styles and Marital Quality Between Spouses - Fatahyah, Yahya; Aqilah, Yusoff; Ahmad Tarmizi, Talib; Sarjit Singh, Darshan Singh; Abdul Hakim, Mohad; Nur Ayuni, Mohd Isa; Muhammad Jazlan, Ahmad Khiri (UNIMAS Publisher, 2021)
The research was aimed to study the relationship between attachment styles and marital quality between spouses. A total number of 52 spouses representing teachers from Sekolah Menengah Agama Daeratul Ma'arifil Wataniah 1 (SMA DMW 1), in Peninsular Malaysia's northwest coast, participated in this study. There were two sets of questionnaires used: Experience in Close Relationship (ECR) and Marital Adjustment Test (MAT). The results showed that there was a significant relationship between attachment styles and spouses' styles. However, there is no relationship between marital satisfaction among spouses, and there is also no relationship between attachment styles and marital satisfaction among spouses. Future research is suggested to enhance the inquiry by moving beyond self-report instruments to develop alternative methods of assessment as some of the questions should be more specifically contextualised for the diverse Malaysian culture.